An evolutive elasto-plastic model for cemented paste backfill. (January 2016) - Cui, Liang; Fall, Mamadou
Abstract: An evolutive elasto-plastic model is developed in this research work to address the vital role of binder hydration in the evolution of the mechanical behavior and properties of cemented paste backfill (CPB). Double hardening/softening parameters, which include effective incremental plastic strain and degree of binder hydration, are adopted. A non-associated plastic potential function based on the dilation angle is employed to formulate the plastic deformation and dilation of CPB. Mechanical parameters, such as cohesion, internal friction and dilation angles, stiffness, and Poisson's ratio are expressed as functions of the degree of binder hydration. The developed model is implemented in a finite element code, COMSOL Multiphysics, and then validated against experimental data obtained from laboratory tests performed in this study and by other researchers. The validation results show good agreement between the predicted and experimental results, thus confirming the capabilities of the new constitutive model to well capture binder hydration induced evolution of the mechanical behavior and properties of CPB.